Elastic carbon dot/polymer films for fluorescent tensile sensing and mechano-optical tuning. (November 2019) - Shauloff, Nitzan; Bhattacharya, Sagarika; Jelinek, Raz
Abstract: Development of simple, readily-applicable sensors for mechanical deformation of polymers is highly sought albeit a formidable task. Here we demonstrate that composite films comprising carbon dots (C-dots) embedded in an elastic polymer host allow fluorescence-based quantitative determination of tensile modulation. Film stretching induced both blue shift in the C-dots' fluorescence peak positions and dramatic increase in fluorescence intensities. The phenomenon was demonstrated for different C-dots exhibiting distinct fluorescence emissions (e.g. colors). Importantly, the C-dot/polymer fluorescence intensity could be quantitatively correlated to tensile parameters, specifically film stress and strain. The direct correlation is ascribed to stretch-induced modulation of the average distances among the polymer-embedded C-dots and concomitant modification of aggregation-induced self-quenching. We further exploited the tensile-dependent fluorescence modulation of the C-dot/polymer system to construct a tunable-intensity white light emitter, opening the way to innovative mechanically-tuned optical device. Graphical abstract: Image 1